Can Peers Improve Agricultural Productivity? - Tisorn Songsermsawas; Kathy Baylis; Ashwini Chhatre; Hope Michelson (Center for Economic Studies and ifo Institute (CESifo), 2014)
Productivity varies greatly among farmers and the source of that variation is not fully understood. Using a unique Indian household survey, we estimate peer effects on agricultural revenue. Results show that 60% of farmers' revenue is explained by peers. Input expenditures and land allocation to cash crops do not fully explain the variation in revenue, implying peers may also affect management, negotiation and marketing strategies. We verify that endogenous network formation, geography, off-farm opportunities and agricultural extension do not drive our results. Peer effects are strongest for agricultural peers and in the cultivation of a new crop.
Keywords: C21; D85; Q12; 330; peer effects; agricultural productivity; India; crop revenue